Workshop Pengenalan Ajeng (Aplikasi Jangan Menyontek G-Score) Guna Menunjang Pembelajaran Online - Aldi Adi Pratama; Adelia Putri Adianingsih; Ajeung Reihan Syafia; Arumaisya An Umillah Arimi; Wahyuni Zefannya Birgita Sitanggang (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
AJENG (Application Don't Cheat Using the Method G-Score) is a platform learning with a virtual approach system using a continuous problem analysis system. Not only that, AJENG has developed various kinds of virtual-based learning services such as learning videos delivered directly by experts, online classes, education games to overcome boredom and an online exam platform that is accompanied by AI technology, namely face and sound detection so that it can reduce cheating activities that often occur, and done by each student. The presence of feature helps game this create a more enjoyable learning atmosphere: Learning While Playing. The system of auto play game this uses the Method G-Score, which is the cumulative ability of students using simple number assessments based on game value skills and test results.